Therapeutical and Nutraceutical Roles of Cyanobacterial Tetrapyrrole Chromophore: Recent Advances and Future Implications - Singh, Kshetrimayum Birla; Kaushalendra,; Rajan, Jay Prakash (Frontiers in Microbiology, 2022)
Abstract Cyanobacteria have attracted the attention of researchers because of their promising role of their primary and secondary metabolites in functional food and drug design. Due to an ever increasing awareness in health and use of natural products to avoid the onset of many chronic and life style metabolic diseases, the global demand for the use of natural drugs and food additives has been increased since last few decades. There are several reports about the high valuable cyanobacterial products such as carotenoides, vitamines, minerals, polysaccharide and phycobiliproteins showing antioxidant, anti-cancerous, anti-inflammatory, hypoglycemic and antimicrobial properties. Recently, it has been shown that allophycocyanin increases the longevity and reduces the paralysis effect at least in Caenorhabditis elegans. Additionally, other pigments such as phycoerythrin and phycocyanine show antioxidative properties. Because of high solubility in water and zero side effects, some of the cyanobacterial tetrapyrrole derivatives i.e. pigments facilitate an innovative and alternative way to beverage and food industries in place of synthetic coloring agents at commercial level. Thus, not only the tetrapyrrole derivatives are essential constituents for the synthesis of most of the basic physiological biomolecules such as haemoglobin, chlorophyll and cobalamine but also has potential to be used for the synthesis of synthetic compounds used in the pharmaceutical and nutraceutical industries. In the present review, we have focused around the different aspects of tetrapyrrole ring in drug design and food industries and have addressed its remaining challenges to be used as natural nutrient supplements and therapeutic agent.